Mastery Level of Basic Concept of Science Course Using STEM-PBL based PHET Simulation Application: Mastery of Concepts; Phet Simulation; STEM-PBL - Ummu Khairiyah; Nur Faizah, Silviana; Permata Dewi, Larasati (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
This study aims to determine the effectiveness of using the Phet Simulation application based on STEM (Science, Technology, Engineering, and Mathematics) – PBL (Problem Based Learning) for mastering the basic concepts of science, especially the subject of Dynamic Electricity. This research was conducted on 1st Semester students from one of the PTKIS in Lamongan who taught the basic science concepts course for the 2022/2023 academic year, namely 35 people. The type of research used is quasi-experimental with a One Group Pretest-Posttest research design. The data collection techniques as the main data are pretest and posttest to find out the increase in mastery of the concept. The hypothesis testing in this study used the Paired Sample t Test using the SPSS 25 application. Based on the data obtained sig.2tailed 0.000 <0.05, it can be concluded that the use of the STEM-PBL-based phet simulation application is effective in increasing students' understanding of concepts